Respons Pertumbuhan, Produksi, dan Kandungan Flavonoid Bawang Dayak (Eleutherine palmifolia) terhadap Pengendalian Gulma dan Jarak Tanam - Vira Irma Sari; Ismail Saleh; Rina Ekawati (Agrotechnology Research Journal, 2020)
Dayak shallot has various phytochemical compounds that useful for health; people use it as medicinal plants. The technique of cultivating plants has not been informed completely. Hence, the research needs to be conducted to understand the competitiveness of weeds and the best planting space for optimal production. The research objectives are to obtain the effect of weed control and plant spacing for Dayak shallot growth and development. This research was used randomized block design two factors. The first factor is plant spacing and the second factor is weed control. There are four combinations of treatments between planting space and weed control. The treatment combinations used are: (1) Plant spacing of 15 cm x 15 cm with weed control; (2) Plant spacing of 15 cm x 15 cm without weed control; (3) Plant spacing of 30 cm x 30 cm with weed control; and (4) Plant spacing of 30 cm x 30 cm without weed control. Each treatment combination was repeated three times. The results showed that a combination of plant spacing and weed control was affected the percentage of flowering, the number of flowers on 4 and 6 days after planting, and the dry weight of Dayak shallot. The components of plant growth of Dayak shallot (plant height, number of leaves, root length, leaf biomass, root biomass, and total flavonoid content) was not affected by the combination of treatments. The dominant weed is Borreria latifolia, with SDR 30.623%.